Indegenous Healer Knowledge About Illness and The Way to Make Traditional Medicine - Regina Marinta Sinaga; Fikarwin Zuska; Panal Sitorus (Indonesian Journal of Medical Anthropology, 2021)
Abstract: This study discusses the knowledge of traditional healers about disease healing techniques and how to make good traditional medicines. The purpose of this study was to describe the knowledge of traditional healers about disease healing techniques and how to manufacture traditional medicines in traditional medicine systems in Medan City. The research method used in data collection is observation and in-depth interviews. The result of this research is that the knowledge of traditional healers about disease healing techniques is a combination of a personalistic medical system and a naturalistic medical system. Knowledge about how to make good traditional medicine (CPOTB) is only based on traditional knowledge (indegenous knowledge) which is still far from quality standards in health services. maximum.